Evaluating dalfampridine for the treatment of relapsing-remitting multiple sclerosis: does it add to the treatment armamentarium?. (24th July 2019) - Foschi, Matteo; Lugaresi, Alessandra
ABSTRACT: Introduction : Multiple sclerosis (MS) is a demyelinating disease, causing axonal damage and disability. Dalfampridine (DAL) is an extended-release formulation of 4-aminopyridine (4AP) and broad-spectrum voltage-dependent potassium channel blocker that is reported to improve motor, visual and cognitive functions. Furthermore, it is presently the only approved drug for walking impairment in MS. Areas covered : Herein, the authors evaluate DAL as a relapsing-remitting MS treatment, reporting and commenting on all aspects of the drug including its chemistry, safety, pharmacokinetics, and cost-effectiveness. A bibliographic search was performed on PubMed using the terms 'dalfampridine OR fampridine OR 4-aminopyridine'. Expert opinion : Evidence from post-marketing studies suggests that DAL, consistent with the effects of 4AP, may not only improve walking speed, but also arm function, fatigue, mood and cognition through restored nerve conduction in central nervous system demyelinated areas. Long-term safety data confirm that the approved dose of 10 mg twice daily is generally well tolerated. However, despite the reported efficacy, the extent of the benefits is limited in real life activities, although significant improvements have been demonstrated in the clinical setting. Patients often complain of side effects (such as cramps and painful paraesthesia) or lack of efficacy. Also, its considerably higher pricing in comparison to 4AP represents an important limitation.